(untitled) (Світ фінансів, 2017)
Івашко О. А. Концептуальні засади організації ТПР та фінансово-правове забезпечення їх інвестиційної діяльності. Розглянуто теоретичні засади організації та функціонування територій пріоритетного розвитку; висвітлено їх роль у реструктуризації економіки; проведено аналіз інвестиційної діяльності на території пріоритетного розвитку. Подано пропозиції щодо удосконалення інвестиційної діяльності на території пріоритетного розвитку; рекомендації щодо основних стратегічних пріоритетів активізації інвестиційної діяльності на територіях пріоритетного розвитку. Ivashko O. Conceptual functions of TPR organization and financial-legal providing of their investment activity. In the article the theoretical bases of organization and functioning of territories of priority development are considered; their role is reflected in restructuring of economy; the analysis of investment activity is conducted on territory of priority development. Suggestions are given in relation to the improvement of investment activity on territory of priority development; recommendations in relation to basic strategic priorities of activation of investment activity on territories of priority development.